Analysis of the Quality of Service on the Level of Satisfaction of the Patient In Rs Umum Bandung and Malahayati Medan in Years 2019 - Basyariah, Afni; Nasution, Sri Lestari Ramadhani; Girsang, Ermi; Nasution, Ali Napiah (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective: This study aims to comparing the analysis of the influence of the treatment of disease specialists in the level of satisfaction of outpatient patients at RSU Malahayati Medan and RSU Bandung year 2019. Methods: This research is a descriptive correlation study. Where this research uses a cross-sectional approach i.e. data that concerns free variables or risks and variable binding or variable consequences, will be collected at the same time. That is, each research subject is only observed once and the measurement is done against the status of character or variable subject at the time of the examination, the author wants to know the influence of reliability, responsiveness, appearance, and attention, in providing service in several type B hospitals in North Sumatera year 2019. Results: Patients who said the specialist disease in the doctor was reliable as much as 38 people (60.3%), less responsive as many as 40 people (63.5%), attention as much as 51 people (81%) and appearances as many as 51 people (81%). Conclusions: Variables that affect the satisfaction rate of the outpatient in the RSU Malahayati Medan and RSU Bandung year 2019 is a variable of reliability and variable attention where the dominant variable affects the level of patient satisfaction is variable reliability, while variables that cannot influence is the responsiveness.